Lateral patellar retinacular release: changes over the last ten years - Leonardo Pini Rosalem Marciano da Fonseca; Ednei Haruo Kawatake; Alberto de Castro Pochini (Revista Brasileira de Ortopedia)
ABSTRACT Lateral retinacular release is a useful resource in knee surgery that can be used for disorders of the extensor mechanism. For many years, it was indiscriminately used in the treatment of the various patellofemoral joint alterations, with conflicting functional results. This study aimed to analyze the changes that have occurred in the indications and clinical effectiveness of lateral retinacular release by reviewing the relevant literature of the past ten years, comparing it to the classic literature on the subject. It was found that less extensive releases decompress the lateral patellar facet, helping with pain control, while decreasing the risks of medial subluxation. Nowadays, there is clear evidence for its indication in the lateral patellar hypercompression syndrome associated with anterior knee pain, as long as there is no related instability; furthermore, it will normally play an adjuvant role in extensor mechanism alignment surgeries for cases of recurrent patellar instability. The initial results for symptomatic patellofemoral osteoarthritis are promising when lateral release is combined with cartilage debridement; in total knee replacement, it is more commonly used for the correction of valgus deformity in order to improve the components’ congruency. Finally, distinguishing the different patellofemoral joint pathologies is seen as crucial in order to indicate this procedure. Further randomized control trials that compare surgical techniques with long-term results are still needed.